Linkages and spillover effects of South African foreign direct investment in Botswana and Kenya - Felix Adamu Nandonde; Richard Adu-Gyamfi; TinayeSonto Mmusi; Herbert Wamalwa; Simplice Asongu; Johannes Pieter Opperman; Jeremiah R. Makindara (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
In recent decades, the impact of South African foreign direct investment in Africa has been captured by research and policy. This paper investigates linkages and spillover effects of South African foreign direct investment in Botswana and Kenya. The study uses primary data to investigate qualitative implications. The findings reveal that South African firms operate in sectors including retail, food-processing, and information and communication technology. Linkages forged in these sectors include supply, employee, joint venture, service, and institutional nexuses. Supply and service linkages create observable spillovers which point to the fact that younger local firms tend to benefit from South African firms in terms of technology transfer and training opportunities. Host country policymakers are therefore encouraged to provide favourable incentives for foreign direct investment to promote entrepreneurship. Other policy implications are also discussed.
Keywords: E23; F21 F30; L96; L98; O55; 330; Botswana; foreign direct investment; Kenya; linkages; South Africa; spillover effects